Freezing Injury and Phospholipid Degradation in Vivo in Woody Plant Cells: I. Subcellular Localization of Phospholipase D in Living Bark Tissues of the Black Locust Tree (Robinia Pseudoacacia L.) - Yoshida, Shizuo (1979)
The subcellular localization of phospholipase D in homogenates of living bark tissues of the black locust tree (Robinia pseudoacacia L.) was examined and found in both soluble and particulate fractions. At least some of the soluble enzyme was considered to be compartmentalized in vacuoles. Considerable amounts of phospholipase D seemed to be tightly bound on several membranes such as endoplasmic reticulum, tonoplast, and a membrane associated with potassium-stimulated ATPase (pH 6.1). The mitochondrial fraction banding at the 40 to 43% (w/w) sucrose layer, however, had the lowest specific activity. The soluble and the particulate phospholipase D were considered to be similar in nature. It is possible that the particulate enzyme, as a part, may be derived from the coexisting nonvesiculated materials visualized in the electron micrograph of each membrane fraction. An involvement of the soluble or the presumed membrane-bound phospholipase D in phospholipid degradation in vivo during freezing at sublethal temperatures was discussed with special reference to freezing injury of plant cells.